An Amorphous Phase of Zinc and Silicon at Composition Zn2Si5(:H, OH). Issue 1 (2nd December 2016) - Feng, Xianjuan; Böhme, Bodo; Bobnar, Matej; Simon, Paul; Carrillo‐Cabrera, Wilder; Burkhardt, Ulrich; Schmidt, Marcus; Schwarz, Ulrich; Baitinger, Michael; Straßner, Thomas; Grin, Yuri
Abstract : An amorphous phase at composition Zn2 Si5 (:H, OH) was prepared by oxidation of the precursor phase Li2 ZnSi at 80 °C in the ionic liquid of n ‐dodecyltrimethylammonium chloride (DTAC) and AlCl3 in 1:1 molar ratio, followed by removal of elemental zinc by dilute aqueous HCl. The product was structurally amorphous according to HRTEM, XRPD, and Raman spectroscopy. Zn2 Si5 (:H, OH) forms layers embedded in a matrix of a silica by‐product. On annealing at 150 °C, amorphous Zn2 Si5 (:H, OH) decomposed into crystalline Zn and α‐Si. The decomposition comes along with the release of H2 revealed by TG‐MS studies. IR and solid‐state NMR spectroscopy revealed that the Zn2 Si5 bulk is terminated by Si‐OH and Si‐H groups. The absence of Knight shift in the 29 Si NMR signal assigned to Zn2 Si5 (:H, OH) suggests semiconducting behavior. Abstract :